Improved quality of life in head and neck cancer patients treated with modern arc radiotherapy techniques – A prospective longitudinal analysis - Chuang, Eva Yu-Hsuan; Hou, Pei-Yu; Shueng, Pei-Wei; Lo, Wu-Chia; Lin, Ping-Yi; Lin, Shih-Chiang; Wu, Po-Hsuan; Jiang, Jing-Gu; Chung, Chen-Shuan; Hsu, Chen-Xiong; Kuo, Deng-Yu; Lu, Yueh-Feng; et al. (Frontiers in Oncology, 2024)
PurposeThe present longitudinal study aimed to evaluate the potential impact of modern radiotherapy (RT) techniques on quality of life (QOL) in patients with head and neck (HNC) cancer.Materials and methodsIn this single-center prospective study, participants were asked to complete QOL questionnaires that included the EORTC QLQ-C30, QLQ-H&N 35 and utility score by time trade-off (TTO) at three time points (2 weeks, 3 months and 6 months) after completion of RT. All patients were treated by modern RT techniques [volumetric modulated arc therapy (VMAT) or helical tomotherapy (HT)]. Patients who developed recurrence or died before the 6-month follow-up were excluded. Linear mixed models with random intercepts for participants and restricted maximum likelihood estimates were used to assess the effect of our study variables (age, sex, primary site, cancer stage, treatment, radiation dose and radiation method). Overall changes in QOL, utility scores and symptom burdens at different time points were tested using paired t tests.ResultsA total of 45 patients were recruited from 2022 to 2023. Those who completed the surveys at 2 weeks with at least 1 follow-up (30 patients, 67%) were enrolled in the final analysis. The majority of these 30 patients were men (76.7%), had oral cancer (40%), had stage III or IV disease (60%), received surgical intervention (63%) and were treated with chemoradiation (80%). A curative total dose of 66 to 70 Gy was delivered to 23 (76.7%) patients, half of whom received HT. Patients who received chemotherapy had significantly lower global QoL scales (mean difference, 27.94; 95% CI, 9.33-46.55; p=0.005). Global QOL, physical function, symptoms of sticky saliva, cough, feelings of illness and weight loss improved significantly between 2 weeks and 3 months. There was no significant difference between 3 and 6 months. Interestingly, improvements in social function, social contact, pain and nutrition reached significance at 6 months. Subgroup analysis revealed greater pain relief over time for patients who underwent HT (p=0.030). Moreover, patients who participated in swallowing rehabilitation programs had a greater decrease in nausea and vomiting (p=0.036).ConclusionHNC patients treated with modern RT techniques experience improved QOL and physical function over time. The most significant improvement occurs between 2 weeks and 3 months, after which the improvement plateaus. However, social function, social contact, pain and nutrition may require longer recovery intervals after treatment. HT with daily image guidance could provide a therapeutic opportunity for improving pain relief in patients with HNC.